Orzeczenie o potrzebie kształcenia specjalnego jako podstawowy dokument organizowania warunków kształcenia specjalnego - Wielebski, Mariusz (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Parents who have children with intellectual disability have many difficulties in getting help for their children. First step is collecting documents, second is delivering to Poradnia Psychologiczno – Pedagogiczna, third waiting for the decision, fourth giving it to school and finally getting help. I try to help them and other people. I show, how is important cooperation between parents-teachers-specialist. If it is well we haven’t any problems and everything is easy and short.